UPAYA PT INDOFOOD CBP SUKSES MAKMUR TBK DALAM MEMPERLUAS PASAR EKSPOR DI AMERIKA SERIKAT - Amalia Azzahra (2024)
PT Indofood CBP Sukses Makmur Tbk is a multinational company from Indonesia that focuses on selling food and beverages. Through investment efforts, joint ventures, collaborations, and holding exhibitions in collaboration with ITPC Chicago and the Indonesian Diaspora, as well as related partners who took part in managing the distribution of Indofood products, one by one their products began to be known and consumed by people in the United States. This research aims to discuss PT Indofood CBP Sukses Makmur Tbk's efforts to expand the export market in the United States using Multinational Corporations (MNC) theory, Comparative Advantage theory, and the Private Sector concept in International Trade. The research method used is a qualitative case study using primary data sources and secondary data. The results of this research show that the expansion of the export market carried out by PT Indofood CBP Sukses Makmur Tbk cannot be separated from the role of the government in Indonesia and the United States. The expansion of the export market produced by PT Indofood CBP Sukses Makmur Tbk produces superior products that are popular with people in the United States, namely Indomie products. And Indomie itself has various flavor variants and cheaper selling prices compared to brands from other countries, so these things have a good impact on Indomie sales and an increase for PT Indofood CBP Sukses Makmur Tbk itself